Do farmer demographics influence their preferred type of communication? - Branco, Lenai (My University, 2020)
Customer satisfaction is an important performance indicator for a company. Given this, a company should devote time and resources to finding ways to provide a unique and differentiated experience to each individual customer based on their preferences. If a company can build a strong profile on each customer, any person within the company that is to be in contact with the customer will be able to provide that customer with their desired preference and increase the overall customer experience. On one hand, the customer preferences are continuously evolving driven by demographic and socio-economic factors, on the other hand technology advancements create new opportunities for connecting with customers. The objective of this study is to gain insights into differences in customer preferences for communication methods. The main variables of interest for the financial institution are the generational groups, distance from the servicing office, segment and crops grown by the farmer. The analysis is based on primary data collected from a sample of 91 customers and their current relationship manager at American AgCredit. Existing data was researched and collected regarding borrowers’ age, location in relation to the closest servicing office, segment within AAC, and crops farmed. Customer preference was then found by interviewing relationship managers for selected customers. Binary logit regression analysis was used to examine the relationship between the independent variables and customers’ preferred communication method. The results indicate that a statistically significant relationship exists between preferred method of contact and age of customer, segment and farmers that farm permanent crops. Results also indicate that younger customers and customers who are further from their servicing office are more inclined to use electronic communication methods, such as phone calls and email, compared to in-person meetings and snail mail. Given the importance of knowing customers’ preferences, these results can help service providers, such as financial institutions, provide their customers with superior communication experience.
Keywords: Demographics; Customer Profile; Agribusiness; Financial Services